English studies from archives to prospects. - Grgas, Stipe, 1951-; Klepač, Tihana; Domines Veliki, Martina (Cambridge Scholars Publishing, 2016)
This volume explores English Studies from the perspective of linguistics and applied linguistics. By examining developments within their selected topics, the authors of these 18 chapters provide a broad overview of English Studies as related to their specific points of interest. Topics range from the well-established, such as negation, grammaticalization, and the role of culture in learning English, to those that are currently being revisited or are considered relatively new, such as corpus analysis, English as a lingua franca, and third language acquisition. The chapters reflect a modern approach to linguistic and applied linguistic phenomena, including diachronic and synchronic perspectives, as well as quantitative and qualitative research paradigms. English Studies as practiced at the English Department in Zagreb during the last 80 years, the anniversary of which instigated the invitation of contributions for this collection, are presented here as a vibrant field, characterized by dynamics and complexities that introduce novel ideas, and help us embrace emerging aspects of more established concepts.